SEVERE POSTURE AND GAIT DISTURBANCE IN LUMBAR SPINAL STENOSIS: A CASE REPORT - Lestari, Dwi Indriani; Anggraini, Vivid Prety; Pringga, Gutama Arya; Kurniawan, Shahdevi Nandar; Misnasari, Putri Priela (Journal of Pain, Headache and Vertigo, 2024)
One of the causes of low back pain is lumbar spinal stenosis (LSS). LSS is defined as a disorder resulting from degenerative processes leading to narrowing of the spinal canal. The nature of pain in LSS—the neurogenic claudication—was aggravated by upright or extended trunk positions, such as during walking, descending stairs, or simply standing. Patient self-adjustments in response to pain can induce further muscle disturbance and worsen the condition. A 56-year-old male suffering from poor posture with antalgic and Trendelenburg gait. The MRI showed multiple spinal canal stenosis with compression of the L4-S1 nerve roots affected the gait and worsened posture. Physical medicine rehabilitation (PMR) program—including the use of ultrasound diathermy for severe muscle spasm followed by muscle stretching, Transcutaneous Electrical Stimulation (TENS) for pain relief, Neuromuscular Electrical Stimulation (NMES) for muscle strength improvement and several therapeutic exercises—has proven beneficial in reducing patient’s symptoms thus correcting the posture and gait. At this point spinal canal narrowing is not only causing pain with neurological deficit but may lead to posture and gait disturbance that increasing the patient's disability. The use of physical modalities combined with exercise has been shown to benefit patients similarly to surgery but without invasive approach.